Selective Vulnerability of the Locus Coeruleus Noradrenergic System and its Role in Modulation of Neuroinflammation, Cognition, and Neurodegeneration - Andrew K. Evans; Erwin Defensor; Mehrdad Shamloo (Frontiers Media S.A., 2022)
Locus coeruleus (LC) noradrenergic (NE) neurons supply the main adrenergic input to the forebrain. NE is a dual modulator of cognition and neuroinflammation. NE neurons of the LC are particularly vulnerable to degeneration both with normal aging and in neurodegenerative disorders. Consequences of this vulnerability can be observed in both cognitive impairment and dysregulation of neuroinflammation. LC NE neurons are pacemaker neurons that are active during waking and arousal and are responsive to stressors in the environment. Chronic overactivation is thought to be a major contributor to the vulnerability of these neurons. Here we review what is known about the mechanisms underlying this neuronal vulnerability and combinations of environmental and genetic factors that contribute to confer risk to these important brainstem neuromodulatory and immunomodulatory neurons. Finally, we discuss proposed and potential interventions that may reduce the overall risk for LC NE neuronal degeneration.